EVALUASI KEBIJAKAN PROSES PEMBANGUNAN PLTN DI SEMENANJUNG MURIA KABUPATEN JEPARA JAWA TENGAH - QIQI ASMARA (NEO POLITEA, 2020)
The main problem that has become a phenomenon in this study is the evaluation of the policy of the process of building a nuclear power plant in the Semenanjung Muria, Jepara Regency, Central Java Province. This policy evaluation is designed to be able to describe the stages of the process, mechanism and objectives of development policy evaluation in the implementation of the construction of nuclear reactors in the Muria Peninsula. The national energy crisis facing the country of Indonesia can be overcome by the existence of alternative energy, namely nuclear power plants. The results of the evaluation conducted by BATAN stated the feasibility of building a nuclear power plant on the Semenanjung Muria, but this contradicts the opinions of the people who strongly reject the process of building a nuclear power plant in their region. This is then the researcher analyzes further and becomes the focus of discussion in this study. This study uses Dunn's policy evaluation theory as an analysis knife in analyzing the policy evaluation of the process of building a nuclear reactor on the Semenanjung Muria. The dimensions of the policy evaluation studied are effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy. This study uses qualitative methods, using primary data and secondary data. Primary data were obtained through in-depth interviews with related parties' perceptions about the policy. Secondary data collected in the form of a chronology of policies, laws and regulations and news about the research theme. The results of this study indicate that the evaluation of nuclear power plant development policies on the Semenanjung Muria has not been effective. This is due to public concern about the dangers of nuclear radiation that may be caused in the operation of nuclear reactors. In addition, problems related to political issues also have an impact on the discrepancy of the results of evaluations conducted by BATAN with the conditions that occur in the field. This continues with the era of reforms which has a direct impact on changing the direction of development and national nuclear policies.